Effectiveness of Virtual Reality Application as English Learning Media - Wibowo, yusep Windhu Ari; Murtopo, Ali; Sari, Dian Puspita (Lingua : Journal of Linguistics and Language, 2024)
In recent years, technological advancements have significantly transformed various aspects of education, including language learning. The application of virtual reality technology greatly encourages learners to have high levels of curiosity. Researchers want to develop English language learning with virtual reality, which has the advantage of students being able to explore the virtual world with conditions exactly like real life in the hospitality industry). Where learners hone their understanding of English through analyzing the virtual world.  In the context of language learning, understanding  the effectiveness and acceptance of innovative instructional approaches is crucial.   Based on the background that has been described, the problem can be formulated as follows, how effective is the application of virtual reality media in improving the English language skills of students at SMK Negeri 1 Abung Selatan. This research practically provides an overview and steps for the use and development of learning models by applying virtual reality,One such cutting-edge technology that has gained increasing attention in the field of language education is Virtual Reality This research measures the effectiveness of the application of Virtual Reality technology with quantitative research methods using an experimental approach.  The subjects in this research are 34 students majoring in Hospitality Accommodation in class XI.1 and 31 students in class XI.2 who take Hospitality English lessons. The majority of respondents feel ease and comfort in their interactions with Virtual Reality, with the advantage that students are able to explore the virtual world with conditions like real life in the hotel industry.   The application of Virtual Reality technology encourages students to have a high curiosity. Most of the students stated that learning using gamification was effective because it was related to the previous topics, fun, easy to understand, accessible, increased enthusiasm and interest for learning. It also did not spend a lot of internet data plans and time.